Реверзибилно инженерство и адитивно производство во проектирањето и производството на сложени делови - Шабани, Бетим (Машински факултет, УКИМ, Скопје, 2020)
Many technological changes have occurred in relation to product development in general. This is due to the high degree of automation and speed of implementation. The same can be said for reverse engineering (RE) and additive manufacturing (AM). In recent years these technologies are being seen as potentially acceptable in different industrial sectors as well as part in actual research and academic activities. RE and AM can be used in different fields, including dentistry and industry. This thesis deals with the theoretical and scientific fundamentals of RE and AM and practical investigation of their use in the design and production of two complex parts: dental bridge and redesigned industrial part. Two selected parts have complex shapes which are appropriate for RE and AM. The dental bridge was measured using 3D scanning technique and reverse engineered, while the original design of the industrial part was optimized using the topology optimization method. Both parts were produced using the laser powder bed fusion (L-PBF) process, where for the dental case, CoCrMo material was used and for the industrial case, AlSi10Mg material was used. The comparison with the traditional technologies of these parts gives the benefits and weaknesses of their implementation in practical aspects. In this thesis, to present a more comprehensive analysis, four main attributes, time, cost, quality, and flexibility were investigated. The design optimization, optimized process parameters, temperature distribution, and total deformation of parts are investigated using numerical analyses. Obtained results were input for experimental work. The production process, metallography, accuracy comparison, and economic aspects are theoretically and experimentally investigated. The obtained results for time, cost, quality, and flexibility were used for comparative analysis with traditional technologies. The dental and industrial parts designed and produced with RE and AM are faster and cheaper produced only when the build job is rationally utilized, but not for single production. Parts produced with RE and AM are more accurate and the whole process is more flexible in comparison with traditional technologies.
Reverse engineering and additive manufacturing in design and production of complex parts
Докторска дисертација одбранета во 2020 година на Машинскиот факултет во Скопје, под менторство на проф. д–р Владимир Дуковски.
Keywords: reverse engineering, additive manufacturing, traditional technologies, time, cost, quality, flexibility